Risk Measure and Forecasting a Return on Investment in Thailand Government Bonds - Budsaba, Kamon; Ongtragoon , Phudit; Saraphan, Danindhorn (Thai Journal of Science and Technology, 2022)
This research aims to find an appropriate risk measure and forecast the return on investment in Thai government bonds. Secondary data of return on investment in Thai government bonds from January 1, 2007, to October 31, 2020, were collected from the Thai Bond Market Association website. Goodness of fit was performed to find the distribution of the rate of return on investment in Thai government bonds to find the suitable measure of risk at 90, 95, and 99 confidence levels. The forecasting of a return of investment in Thai government bonds was done by ARMA-model selected from the appropriate forecasting model selection command using Bayesian information criterion in SPSS version 26. It was found that the conditional value at risk is a suitable risk measure for the rate of return on investment in Thai government bonds dataset. For forecasting the return on investment in the Thai government bonds, the predicted value is very close to the actual value, according to the mean absolute percentage error, which is less than 1 percent.